Uji Toksisitas Akut Ekstrak Etanol Daun Sirsak (Annona muricata L.) Terhadap Ginjal Mencit - salim, Emil; Dewi, Puteri Nigie Kemala; Ginting, Herawaty (Indonesian Journal of Pharmaceutical and Clinical Research, 2023)
Soursop leaf ethanol extract was reported to have immunomodulatory, antidiabetic, anti-inflammatory, lowering uric acid and cholesterol levels properties. Based on these reports, soursop leaf ethanol extract has the potential to be developed into a standardized herbal medicine. To ensure safety, this extract must undergo toxicity studies before marketing. This study examined soursop leaf ethanol extract acute toxicity. LD50 was estimated using the Reed and Muench method, and the effect of the extract on the kidneys was observed. This study used 50 mice—25 males and 25 females—divided into 5 groups. The control group received sodium carboxymethyl cellulose (CMC-Na) 0.5% w/v, and the treatment groups received ethanol extract of soursop leaves at doses of 500, 1000, 1500, and 2000 mg/kg bw orally on the first day, then body weight and number of deaths were calculated and the toxic symptoms were observed over 14 days. After 14 days, the surviving mice were sacrificed to examine the relative organ weights, macropathology and histopathology of the mice kidneys. Male and female mice in the 1500 and 2000 mg/kg bw dose groups showed toxic symptoms. There was no significant difference in relative organ weight at 14 days between groups. The results of organ macropathology showed no colour differences in all groups. Based on histopathological examination, mild damage to the kidney organs can be seen at doses of 1500 and 2000 mg/kg bw and the LD50 result was 1819 mg/kg bw. In conclusion, soursop leaf ethanol extract has a mild toxic effect on mice.